Respuesta :

Hello!

(this took me 20 minutes to type out from what I wrote on paper lol)

I'm going to guide you through this one step at a time

Step 1: Simplify both sides of the equation.

2.3(6−x)+22 = 96−2.3(2x+12)

(2.3)(6)+(2.3)(−x)+22 = 96+(−2.3)(2x)+(−2.3)(12) (use distributive property of multiplication)

13.8+−2.3x+22 = 96+−4.6x+−27.6

(−2.3x)+(13.8+22) = (−4.6x)+(96+−27.6) (Combine The Like Terms)

−2.3x+35.8 = −4.6x+68.4

−2.3x+35.8 = −4.6x+68.4

Step 2: now, add 4.6x to both sides.

−2.3x+35.8+4.6x = −4.6x+68.4+4.6x

2.3x+35.8 = 68.4

Step 3: next, subtract 35.8 from both sides.

2.3x+35.8−35.8 = 68.4−35.8

2.3x = 32.6

Step 4: Divide both sides by 2.3.

[tex]\frac{2.3X}{2.3}[/tex] = [tex]\frac{32.6}{2.3}[/tex]

fractions solved: x = 14.173913

your final answer is: x = 14.173913

I hope this helps, and have a nice day!